Digital Technologies for Quality Assurance in the Construction Industry: Current Trend and Future Research Directions towards Industry 4.0 - Frank Ato Ghansah; David John Edwards (Buildings)
Despite the growing rich and fragmented literature focusing on quality assurance (QA) and Industry 4.0, the implementation of associated individual digital technologies has not been fully evaluated and synthesised to achieve adequate QA in the construction industry; hence, it has received limited focus. This study, thus, aimed to organise, evaluate, and synthesise the current literature on individual digital technology applications in QA in the construction industry and propose future research directions. A literature review approach was adopted for this study along with Deming’s cycle framework to address four research questions: (1) What is the status of the state-of-the-art in the literature? (2) What digital technologies have been applied for QA in the construction industry? (3) Which areas in QA processes have experienced digital technology applications, and what are the applications? (4) What are the limitations of the existing studies and future research directions of digital technologies for QA in the construction industry? The findings showed an increasing trend of research on digital technology for QA in construction since 2017. This cuts across 23 countries with six different research methods published across 18 different publication sources. Four categories of digital technologies were revealed to have been adopted for QA in construction based on the functionality of the technologies: data collection technologies, decision-oriented technologies, collaborative technologies, and transparency and security-related technologies. Evaluation with Deming’s cycle framework revealed that digital technologies have a high level of application at the “do” phase, improving the quality management process during construction towards achieving pre-stated quality requirements. This includes mostly collaborative technologies, consisting of BIM technologies. Limitations of the existing studies were further identified, and this led to five research directions: interoperability of technology development, integrated digital technologies for QA of prefabricated and modular construction, integrated digital technologies for QA of cross-border construction logistics and supply chain, digital innovation for sustainable QA, and moving beyond the technical solution. The study showed a significant contribution to both academia and the industry in the built environment.